(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
To evaluate the influence of guided-inquiry technique on students' academic progress in practical Chemistry, this study used a quasi-experimental design, specifically pre-test, post-test, non-equivalent control group. The study was directed by two research questions and two null hypotheses. A total of fifty SS2 students were randomly selected from seven public secondary schools in the Okrika local government region for the experimental and control groups. Chemistry achievement test (CAT) based on acid-base titration on volumetric analysis was used to obtain results. Two science education professionals verified the instrument. The instrument's dependability was verified using the testretest method, and the scores obtained were correlated using the Pearson correlation coefficient, which yielded an index of 0.75. The mean (X) and standard deviation (SD) statistics were used to answer the study questions, while the null hypotheses were tested at the 0.05 level of significance using analysis of covariance (ANCOVA). The data analysis results revealed a significant difference in mean achievement scores in favor of the experimental group. Second, in terms of gender mean achievement, males outperformed their female counterparts. It was consequently recommended that Chemistry professors involve their students more in guided-inquiry approaches for better teaching and learning in Chemistry.